Effect of attendance on performance in postgraduate courses in science and engineering (2012)
Most postgraduate students in developing countries like Nigeria are working class students that have to shuttle between their workplaces and classes. Reason being that there few or no sponsors for postgraduate programmes exist in the country. Therefore, most students are self sponsored. Furthermore, most postgraduate courses in Nigeria are full time programmes. There are some core courses that require strict attendance in classes. However, it is seen that this is not always the case as the students have to attend to their jobs as well; otherwise they might lose the jobs and have no fund to continue. The programmes considered in this study are those in Statistics and Petroleum Engineering. This study therefore looks at the effect of students’ attendance in postgraduate classes to their performances, and also proffers solutions to its long-term effects on the industrial and economic developments.